ANALISIS IMPLEMENTASI KEBIJAKAN BPJS KESEHATAN TERHADAP PELAYANAN PUSKESMAS (TYPE PERAWATAN) di KOTA MEDAN - Tiur Rajagukguk; Selamat Siregar (JURNAL MANAJEMEN, 2019)
The aim of this study was to determine the purpose of the implementation of the Health BPJS policy on Puskemas services (type of care) in Medan. Statistical analyses in this study were published: validity and reliability test, classic assumption test, factor analysis, SEM analysis, model suitability test, hypothesis test using software SmartPLS ver 3.2.1. R-Square value of 0.642 calculated the model is strong enough, means that the variable implementation of the health policy BPJS (X) which is able to be approved by the service variable Puskesmas (Y) of 64.20%. The results on the path coefficient appear as variables implementing BPJS health policies (X) have a positive relationship with the service variable Puskesmas (Y) with a coefficient value of 0.802 and show a significant influence on Puskesmas service (Y) with a significant p-value of 0,000. The p-value is smaller than the alpha value (5%). Associated with variables that implement health BPJS (X) policies affect positively and significant to the Puskesmas (Y) service variable.